BEBERAPA SIFAT IDEAL GELANGGANG POLINOM MIRING: SUATU KAJIAN PUSTAKA - KAMAL AMIR, AMIR (Jurnal Matematika; Vol 1 No 1 (2010), 2012)
Let R be a ring with identity 1 and s be an endomorphism of R and d be a left s - derivation . The skew polynomial ring over R in an indeterminate x is: R[x;s ,d ] = { f (x) = anxn +L+ a0 | ai Î R} with xa =s (a)x +d (a) The aim of this research is to investigate the ideals in the above skew polynomial ring in case of d = 0 . Precisely, we will investigate the following: (1) the ideal of skew polynomial ring D[x;s ] ; (2) the ideal prim of skew polynomial ring K[x;s ] ; and (3) the s - prim ideal of skew polynomial ring D[x;s ] .
Keywords: automorphism, integral area, s - prim.